Psychometric properties of the Adult Primary Care Assessment Tool Short form (PCAT-S) among high-risk patients in Australian general practice - Chau M. Bui; Marijka J. Batterham; Judy Mullan; Gregory Peterson; Christine Metusela; Jan Radford; Simon Eckermann; Danielle Mazza; Grant Russell; Andrew Bonney (PLoS ONE, 2026)
Introduction The Primary Care Assessment Tool (PCAT) is designed to assess a patient’s experience with primary care across various core and ancillary domains, including First contact – Utilization, First contact – Access, Ongoing Care, Coordination, Comprehensiveness (services provided), Family-centeredness, Community Orientation, and Cultural Competence. This study examined the psychometric properties of the Adult Primary Care Assessment Tool Short Form (PCAT-S) in the Australian general practice setting. Method Data included 715 participants from the EQuIP-GP study, a cluster randomized controlled trial (RCT) conducted with adults aged 18–65 years with a chronic illness or aged over 65 years, from 34 general practices across Australia. For each subscale we assessed internal consistency using Cronbach’s alpha. Factor structure of the PCAT-S instrument was assessed through confirmatory and exploratory factor analysis, using three samples with different methods for handling ‘don’t know/can’t remember’ responses. Results The findings were mixed. Specifically, the subscales related to First Contact – Utilization, Ongoing Care and Comprehensiveness, demonstrated satisfactory internal consistency. However, the remaining subscales showed weak internal consistency. Confirmatory factor analysis indicated potential model misspecification, while exploratory factor analysis generally supported the hypothesized factor structure, albeit with some observed deviations. Conclusions The findings indicate the PCAT-S shows promise as an instrument to evaluate primary care experiences in Australia. However, the observed variability in internal consistency, along with issues identified in confirmatory and exploratory factor analyses, highlight the need for further validation and refinement in this population. Further research is required to address the identified limitations and enhance the tool’s applicability within the Australian general practice context.